Clonal hematopoiesis of indeterminate potential and cardiovascular diseases: A review - Nagendra Boopathy Senguttuvan; Vinodhini Subramanian; Muralidharan TR; Kavitha Sankaranarayanan; Vettriselvi Venkatesan; Thanikachalam Sadagopan (Indian Heart Journal)
Cardiovascular disease (CVD) is a major driver of mortality and declining health worldwide. Cardiovascular diseases (CVD) is the most common cause of morbidity and mortality globally. Although dyslipidemia, smoking, diabetes, hypertension and obesity are some well-known causes of CVD, the overlapping genetic pathways between other diseases and those affecting cardiovascular health have been overlooked.In the past decade, mutations in TET2, DNMT3A, ASXL1, and JAK2 are found to cause clonal hematopoiesis of intermediate potential (CHIP), a disease associated with age-related haematological malignancies without the presence of cytopenias or dysplasia. Coronary artery disease, heart failure, aortic stenosis, and arrhythmias have been shown to be associated with the presence of CHIP mutations. Addressing the association between CHIP could significantly reduce residual risk patients with CVD. The link between CHIP and CVD can potentially be addressed through inhibitors of inflammasomes, antagonists in the interleukin pathway, or direct antagonists of CHIP mutations.